Strategic uses of social media for improved customer retention - Al-Rabayah, Wafaa, 1985-; Khasawneh, Rawan, 1989-; Abu-Shamaa, Rasha, 1982- (Hershey : Business Science Reference, 2017)
"This book is a pivotal reference source for the latest scholarly research on the implementation of online social networks in modern businesses and examines how such networks allow for a better understanding of clients and customers"--
Social media as a new emerging tool of marketing / Rawan T. Khasawneh, Jordan University of Science and Technology, Jordan -- Towards a framework for integrating social media, customer relationship, and knowledge management / Olayiwola W. Bello, University of Ilorin, Nigeria, Modupe Folarin, City University London, UK, Nasir Faruk, University of Ilorin, Nigeria -- Social customer relationship management (SCRM) : a strategy for customer engagement / Ameen Al-Azzam, Technical College in Tai'f, Saudi Arabia, Rawan Khasawneh, Jordan University of Science and Technology, Jordan -- Marketing on tumblr : where it helps to be honest (and weird) / Kristen Smirnov, Whittier College, USA -- The effect of social networks on branding : a factorial analysis approach / Meriem Nouala, Sidi Bel Abbes University, Algeria, Marwa Imene Mekki, Sidi Bel Abbes University, Algeria / Abdelmadjid Ezzine, Sidi Bel Abbes University, Algeria -- Social media as social customer relationship management tool : case of Jordan Medical Directory / Wafaa A. Al-Rabayah, Independent Researcher, Jordan -- Determinants of brand recall in social networking sites / Kaan Varnali, Istanbul Bilgi University, Turkey, Vehbi Gorgulu, Istanbul Bilgi University, Turkey -- The impact of social media on customer engagement with U.S. banks / Arturo Haro-de-Rosario, University of Almeria, Spain, Laura Saraite, University of Almeria, Spain, Alejandro Saez-Martin, University of Almeria, Spain, Maria del Carmen Caba-Pérez, University of Almeria, Spain -- Social networks impact on potential customers' buying decisions and current customer loyalty / Wafaa A. Al-Rabayah, Independent Researcher, Jordan -- Opinion mining a tool for understanding customers : challenges and approaches / Rawan Khasawneh, Jordan University of Science and Technology, Jordan, Izzat Alsmadi, Boise State University, USA -- Sentiment analysis of social media as tool to improve customers' retention / Wafaa A. Al-Rabayah, Independent Researcher, Jordan, Ahmad Al-Zyoud, Yarmouk University, Jordan -- Can the usage of social media increase the gregariousness of the family to grow successful family-owned businesses? : the usefulness of social media in growing a family-owned business / Mambo Governor Mupepi, Grand Valley State University, USA, Patience Taruwinga, Saint Joseph College, USA, Wafaa A. al-Rabayah, Independent, Jordan -- Using social strategy to retain customers : cases and tips / Wafaa A. Al-Rabayah, Independent Researcher, Jordan.
Includes bibliographical references (pages 264-301) and index.
Keywords: Customer relations -- Technological innovations; Online social networks in business; Social media -- Economic aspects; Branding (Marketing)